English Communication Needs of Hotel Receptionists in Supporting Green Tourism - Ardana, I Komang; Putu Agus Murtono (Universitas Veteran Bangun Nusantara, 2025)
This study explores the English communication needs of hotel receptionists in supporting the implementation of green tourism practices. Using a qualitative research approach, data were collected through interviews, observations, and document analysis in three eco-certified hotels. The findings reveal that English communication is crucial not only for routine guest interactions but also for promoting environmental awareness and encouraging sustainable behavior among international visitors. Receptionists perform various communicative tasks, including explaining eco-friendly programs, persuading guest participation, and clarifying sustainability policies. However, they face challenges such as limited environmental vocabulary, cross-cultural communication barriers, and insufficient institutional training. Despite these limitations, receptionists employ adaptive strategies such as language simplification, visual aids, and contextualization to convey sustainability messages effectively. The study highlights the need for specialized English for Specific Purposes (ESP) programs that integrate environmental and intercultural communication skills. It concludes that empowering hotel receptionists with targeted language training enhances not only service quality but also the hotel’s capacity to promote sustainable tourism values. Thus, effective English communication serves as both a linguistic tool and a strategic means of fostering green tourism in the hospitality industry.